Viral suppression and HIV transmission in serodiscordant male couples: an international, prospective, observational, cohort study. Issue 8 (August 2018) - Bavinton, Benjamin R; Pinto, Angie N; Phanuphak, Nittaya; Grinsztejn, Beatriz; Prestage, Garrett P; Zablotska-Manos, Iryna B; Jin, Fengyi; Fairley, Christopher K; Moore, Richard; Roth, Norman; Bloch, Mark; Pell, Catherine; et al.
Summary: Background: Evidence on viral load and HIV transmission risk in HIV-serodiscordant male homosexual couples is limited to one published study. We calculated transmission rates in couples reporting condomless anal intercourse (CLAI), when HIV-positive partners were virally suppressed, and daily pre-exposure prophylaxis (PrEP) was not used by HIV-negative partners. Methods: In the Opposites Attract observational cohort study, serodiscordant male homosexual couples were recruited from 13 clinics in Australia, one in Brazil, and one in Thailand. At study visits, HIV-negative partners provided information on sexual behaviour and were tested for HIV and sexually transmitted infections; HIV-positive partners had HIV viral load tests, CD4 cell count, and sexually transmitted infection tests done. Viral suppression was defined as less than 200 copies per mL. Linked within-couple HIV transmissions were identified with phylogenetic analysis. Incidence was calculated per couple-year of follow-up, focusing on periods with CLAI, no use of daily PrEP, and viral suppression. One-sided upper 95% CI limits for HIV transmission rates were calculated with exact Poisson methods. Findings: From May 8, 2012, to March 31, 2016, in Australia, and May 7, 2014, to March 31, 2016, in Brazil and Thailand, 358 couples were enrolled. 343 couples had at least one follow-up visit and were followed up for 588·4 couple-years. 258 (75%) of 343 HIV-positive partners had viral loads consistently less than 200 copies per mL and 115 (34%) of 343 HIV-negative partners used daily PrEP during follow-up. 253 (74%) of 343 couples reported within-couple CLAI during follow-up, with a total of 16 800 CLAI acts. Three new HIV infections occurred but none were phylogenetically linked. There were 232·2 couple-years of follow-up and 12 447 CLAI acts in periods when CLAI was reported, HIV-positive partners were virally suppressed, and HIV-negative partners did not use daily PrEP, resulting in an upper CI limit of 1·59 per 100 couple-years of follow-up for transmission rate. Interpretation: HIV treatment as prevention is effective in men who have sex with men. Increasing HIV testing and linking to immediate treatment is an important strategy in HIV prevention in homosexual men. Funding: National Health and Medical Research Council; amfAR, The Foundation for AIDS Research; ViiV Healthcare; and Gilead Sciences.